2008
DOI: 10.1097/ccm.0b013e3181652edd
|View full text |Cite
|
Sign up to set email alerts
|

Electrical impedance tomography compared with thoracic computed tomography during a slow inflation maneuver in experimental models of lung injury*

Abstract: Electric impedance tomography allows assessment of regional ventilation distribution and recruitment in experimental models of direct and indirect acute lung injury as well as normal lungs. Except for pigs with direct acute lung injury, regional ventilation delay determined during a slow inflation from impedance time curves appears to be a simple index for clinical monitoring of alveolar recruitment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
150
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(165 citation statements)
references
References 30 publications
3
150
0
4
Order By: Relevance
“…As EIT is non-invasive and virtually causes no adverse side effects (lack of radiation, no transport required), the method has become an attractive alternative to computed tomography, magnetic resonance imaging or ultrasound examinations. Many comparative medical trials have proved that the EIT results are reliable and repeatable [21][22][23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…As EIT is non-invasive and virtually causes no adverse side effects (lack of radiation, no transport required), the method has become an attractive alternative to computed tomography, magnetic resonance imaging or ultrasound examinations. Many comparative medical trials have proved that the EIT results are reliable and repeatable [21][22][23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Th ey found that the recruitment maneuver was more eff ective for opening collapsed alveoli in extrapulmonary compared to pulmonary ALI, improving lung mechanics and oxygenation with limited damage to alveolar epithelium. Using electrical impedance and computed tomography (CT) to assess lung ventilation and aeration, respectively, Wrigge et al [19] suggested that the distribution of regional ventilation was more heterogeneous in extrapulmonary than in pulmonary ALI during lung recruitment with slow inspiratory fl ow. However, this phenomenon and the claim that recruitment maneuvers are useful to protect the so called 'baby lung' , i.e., the lung tissue that is usually present in ventral areas and receives most of the tidal ventilation, has been recently challenged.…”
Section: Nature and Extent Of Lung Injurymentioning
confidence: 99%
“…RVD has been shown to give accurate data during 12-mL/kg slow insufflation manoeuver by Wrigge [123], later confirmed by Muders [125]. In our case, the data were from spontaneously breathing patients, therefore we cannot know with certainty that the RVD index relates to cyclic opening and closing of the alveoli.…”
Section: Limitations Of the Studymentioning
confidence: 56%
“…Using TVar as one of EIT measures of ventilation distribution has been demonstrated by a number of studies [56,122,123] to provide valid information about the percentage of tidal volume in different parts of the lung.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation